2003
DOI: 10.1167/iovs.02-1092
|View full text |Cite
|
Sign up to set email alerts
|

Placental Growth Factor, a Member of the VEGF Family, Contributes to the Development of Choroidal Neovascularization

Abstract: These observations demonstrate the participation of PlGF in experimental CNV. They identify therefore PlGF as an additional promising target for ocular antiangiogenic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
202
0
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(218 citation statements)
references
References 32 publications
5
202
0
11
Order By: Relevance
“…It has become increasingly evident that no single anti-angiogenic agent (including angiostatin and endostatin) used as monotherapy in preclinical models is able to reduce tumor burden once tumors have reached 100 mm (36). It was shown that the absence of placental growth factor, uPA, or tissue plasminogen activator significantly decreased the development of experimental choroidal neovascularization compared with wild type or uPAR-deficient mice (37). This effect was suggested to be partly due to a modulation of matrix metalloproteinase activity.…”
Section: Figmentioning
confidence: 99%
“…It has become increasingly evident that no single anti-angiogenic agent (including angiostatin and endostatin) used as monotherapy in preclinical models is able to reduce tumor burden once tumors have reached 100 mm (36). It was shown that the absence of placental growth factor, uPA, or tissue plasminogen activator significantly decreased the development of experimental choroidal neovascularization compared with wild type or uPAR-deficient mice (37). This effect was suggested to be partly due to a modulation of matrix metalloproteinase activity.…”
Section: Figmentioning
confidence: 99%
“…The cDNAs were amplified in a 50-μl reaction volume containing 20 mmol/l Tris-HCl (pH 8.4), 50 mmol/l potassium chloride, 1.5 mmol/l magnesium chloride, 0.2 mmol/l of each of the dNTPs and 0.5 μmol/l of each appropriate primer: GGCGATGAGAATCTGCACTGT-3′ (forward), 5′-CA CCTTTCCGGCTTCATCTTC-3′ (reverse) for PLGF [17]; 5′-CAAGTGGCCAGAGGCATGGAGTT-3′ (forward), 5′-GATGTAGTCTTTACCATCCTGTTG-3′ (reverse) for VEGFR-1 [18]; 5′-GAGGGCCTCTCATGGTGATTGT-3′ (forward), 5′-TGCCAGCAGTCCAGCATGGTCTG-3′ (reverse) for VEGFR-2 [18]; and 5′-AGGAGAAGCTTGC TACGTC-3′ (forward), 5′-AGGGGCCGGACTCGTCATAC-3′ (reverse) for β-actin, and 2 U Taq polymerase (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…A possible implication of these findings is that PlGF blockade might inhibit disease processes more selectively than physiological homeostasis and thus evoke fewer side effects. We summarize below the findings on PlGF's (Foidart et al 2009;Furuya et al 2011) Heart PlGF-induced revascularization of ischemic myocardium and vessel enlargement in remote myocardium preserve cardiac performance following infarction (Luttun et al 2002;Kolakowski et al 2006;Roncal et al 2008) Knockout: impaired angiogenesis and inflammation in infarct border (Carmeliet et al 2001) Knockout: Normal exercise induces angiogenesis (Gigante et al 2004) Skeletal muscle PlGF protein or gene delivery: enhances angiogenesis, collateral growth, and blood flow in ischemic limb (Luttun et al 2002;Pipp et al 2003;Babiak et al 2004); restores microcirculation in aged dystrophic muscle (Gargioli et al 2008) Knockout: impaired collateral growth in ischemic limb (Carmeliet et al 2001;Scholz et al 2003;Gigante et al 2006) Knockout: normal exercise-induced angiogenesis (Gigante et al 2004) Eye PlGF prevents vessel obliteration in hyperoxia without including neovascularization (Shih et al 2003) Local ocular PlGF protein or gene transfer causes hematoretinal barrier breakdown and edema (Miyamoto et al 2007;Kowalczuk et al 2011) Knockout or aPlGF: impaired choroidal neovascularization (Carmeliet et al 2001;Rakic et al 2003;Van de Veire et al 2010) Knockout or aPlGF does not impair retinal vascularization during development (Carmeliet et al 2001;Feeney et al 2003 (Carmeliet et al 2001;Scholz et al 2003;Gigante et al 2006) (Eriksson et al 2002;Xu et al 2006;Schomber et al 2007;Tarallo et al 2010) PlGF educates CD34 þ progenitors to proangiogenic CD11b þ myelomonocytes in breast cancer (Laurent et al 2011...…”
Section: Plgf a Disease-modifying Candidatementioning
confidence: 99%
“…PlGF is elevated in human AMD and mouse models of laser-induced CNV (Rakic et al 2003;Huang et al 2011), whereas PlGF gene deficiency in mice reduces experimental CNV (Rakic et al 2003). Current treatment of CNV in human AMD by VEGF blockade offers visual improvement but requires intravitreal injection and can increase the risk of stroke, ischemic heart disease, and adverse ocular events (Mitchell et al 2010).…”
Section: Diseases With Improved Outcome Following Plgf Blockade Oculamentioning
confidence: 99%